The Influence Of Work Environment, Rewards And Teamwork On Employee Performance Of PT Bank Syariah Indonesia Bengkulu Branch - Fitra, Jecky; Susena , Karona Cahya; Monique , Eska Prima (Tractare: Jurnal Ekonomi-Manajemen, 2024)
Bank Syariah Indonesia is a bank in Indonesia that operates in the field of Islamic banking. In this research, there are several obstacles or issues, one of which is the influence of the work environment on the performance of employees at PT. Bank Syariah Indonesia Bengkulu Branch, rewards affecting employee performance at PT. Bank Syariah Indonesia Bengkulu Branch, the work environment influencing employee performance at PT. Bank Syariah Indonesia Bengkulu Branch, and the work environment, rewards, and teamwork affecting employee performance at PT. Of course, within these issues, there are several research objectives, which are to determine the influence of the work environment on the performance of the employees, to understand the influence of rewards on employee performance at PT. Bank Syariah Indonesia Bengkulu Branch, to ascertain the influence of the work environment on employee performance at PT. Bank Syariah Indonesia Bengkulu Branch, and to explore the influence of the work environment, rewards, and teamwork on employee performance at PT. Bank Syariah Indonesia Bengkulu Branch. The type of research used in this study is descriptive method, which is conducted to describe and interpret the objects as they are. The results of the study indicate that based on the research results, the values of X1, X2, and X3 show that more than X = 0.05, as can be seen from X1, X2, and X3, which partially influence employee performance (Y). There is a simultaneous or collective influence of the variables of the work environment, rewards, and teamwork on employee performance (Y) at PT. Bank Syariah Indonesia Bengkulu Branch, with the value of Fsig < α 0.05 and Fcount > F table (16.373 > 2.83), thus it can be concluded that collectively, the independent variables influence the dependent variable.